Association of socioeconomic status with outcomes in older adult community-dwelling patients after visiting the emergency department: a retrospective cohort study. Issue 12 (26th December 2017) - Wachelder, Joyce J H; van Drunen, Isabelle; Stassen, Patricia M; Brouns, Steffie H A; Lambooij, Suze L E; Aarts, Mieke J; Haak, Harm R
Abstract : Objectives: Older adults frequently visit the emergency department (ED). Socioeconomic status (SES) has an important impact on health and ED utilisation; however, the association between SES and ED utilisation in elderly remains unclear. The aim of this study was to investigate the association between SES in older adult patients visiting the ED on outcomes. Design: A retrospective study. Participants: Older adults (≥65 years) visiting the ED, in the Netherlands. SES was stratified into tertiles based on average household income at zip code level: low (<€1800/month), intermediate (€1800–€2300/month) and high (>€2300/month). Primary outcomes: Hospitalisation, inhospital mortality and 30-day ED return visits. Effect of SES on outcomes for all groups were assessed by logistic regression and adjusted for confounders. Results: In total, 4828 older adults visited the ED during the study period. Low SES was associated with a higher risk of hospitalisation among community-dwelling patients compared with high SES (adjusted OR 1.3, 95% CI 1.1 to 1.7). This association was not present for intermediate SES (adjusted OR 1.1, 95% CI 0.95 to 1.4). Inhospital mortality was comparable between the low and high SES group, even after adjustment for age, comorbidity and triage level (low OR 1.4, 95% CI 0.8 to 2.6, intermediate OR 1.3, 95% CI 0.8 to 2.2). Thirty-day ED revisits among community-dwelling patients were also equal between the SES groups (low: adjusted OR 1.0, 95% CI 0.7 to 1.4, and intermediate: adjusted OR 0.8, 95% CI 0.6 to 1.1). Conclusion: In older adult ED patients, low SES was associated with a higher risk of hospitalisation than high SES. However, SES had no impact on inhospital mortality and 30-day ED revisits after adjustment for confounders.